State and federal standards for mobile source emissions (National Academies Press, 2006)
Emissions from mobile sources contribute significantly to air pollution in the United States. Such sources include cars and light- and heavy-duty trucks; diesel-powered cranes, bulldozers, and tractors; and equipment such as lawnmowers that run on small gasoline engines. The role of state versus federal government in establishing mobile-source emissions standards is an important environmental management issue. With this in mind, Congress called on EPA to arrange an independent study of the practices and procedures by which California develops separate emissions standards from the federal government and other states choose to adopt the California standards. The report provides an assessment of the scientific and technical procedures used by states to develop or adopt different emissions standards and a comparison of those policies and practices with those used by EPA. It also considers the impacts of state emissions standards on various factors including compliance costs and emissions. The report concludes that, despite the substantial progress in reducing emissions from mobile sources nationwide, more needs to be done to attain federal air-quality standards in many parts of the country. Additionally, California should continue its pioneering role in setting emissions standards for cars, trucks, and off-road equipment.